Construction of a [NiFe]-hydrogenase deletion mutant of Desulfovibrio vulgaris Hildenborough. (1st February 2005) - Goenka, A.; Voordouw, J.K.; Lubitz, W.; Gärtner, W.; Voordouw, G.
Abstract : A mutant of Desulfovibrio vulgaris Hildenborough lacking a gene for [NiFe] hydrogenase was generated. Growth studies, performed for the mutant in comparison with the wild-type, showed no strong differences during the exponential growth phase. However, the mutant cells died more rapidly in the stationary growth phase.